Staphylococcus aureus bacteremia in patients with prosthetic devices: costs and outcomes. - Chu, V; Crosslin, DR; Friedman, J; Reed, S; Cabell, C; Griffiths, R; Masselink, L; Kaye, K; Corey, G; Reller, L; Stryjewski, M; Schulman, K; et al. (2005)
PURPOSE: Although Staphylococcus aureus is a leading cause of nosocomial infection, little is known about the impact of S. aureus bacteremia on patients with prosthetic devices. This investigation sought to define the clinical outcome, health care resource use, and infection-associated costs of S. aureus bacteremia in patients with prostheses. SUBJECTS AND METHODS: All hospitalized patients with a prosthetic device and S. aureus bacteremia during the 96-month study period were identified prospectively. Clinical data were collected at the time of hospitalization. Data regarding infection-related resource utilization and infection-related costs within 12 weeks of the initial bacteremia were also recorded. RESULTS: 298 patients with > or =1 prosthesis and S. aureus bacteremia were identified (cardiovascular device--122 patients, orthopedic device--73 patients, long-term catheter--71 patients, and other devices-32 patients). Overall, 58% of patients underwent surgery as a consequence of the infection. Infection-related complications occurred in 41% and the overall 12-week mortality was 27%. The mean infection-related cost was 67439 dollars for patients with hospital-acquired S. aureus bacteremia and 37868 dollars for community-acquired S. aureus bacteremia (cost difference 29571 dollars; 95% confidence interval, 14370 dollars-49826 dollars). Rates of device infection, complications, 12-week mortality, and mean cost varied by prosthesis type. CONCLUSION: S. aureus bacteremia in patients with prosthetic devices is associated with frequent complications, substantial cost, and significant health care resource utilization.